L’écriture créative partagée : une voie d’intervention à l’école primaire - Sirois, Pauline; Vanlint, Alice; Gravel, Anne-Sophie (Canadian Journal of Education/Revue canadienne de l’éducation, 2024)
This scientific article presents the outcomes of a longitudinal study experimenting with a developmental pedagogical approach in writing with primary school students. The students’ progress is assessed by analyzing fictional stories written by the children at different points in time and in two distinct contexts, one with a predefined structure, and one without. The outcomes of the students identified as struggling at the beginning of the study are compared to those of their peers who were considered as having no difficulties. The analysis carried out, besides highlighting the contribution of the approach, makes it possible to question current evaluation and intervention practices, which often rely on a step-by-step and rigid conception of writing.